Functional recovery of regional myocardial deformation in patients with takotsubo cardiomyopathy. Issue 1 (July 2017) - Kim, Sung-Ai; Jo, Sang-Ho; Park, Kyoung-Ha; Kim, Hyun-Sook; Han, Sang-Jin; Park, Woo-Jung
Abstract: Background: Takotsubo cardiomyopathy (TC) is acute, but completely reversible in the absence of significant coronary artery disease. This study aims to assess the functional recovery of regional myocardial deformation in patients with TC using 2-dimensional (2D) speckle tracking echocardiography. Methods: Thirty-three patients diagnosed with TC (mean age 63 years, 26 female) prospectively underwent serial 2D echocardiography on day 1 (initial presentation), day 4 [the middle, interquartile range (IQR), 2–5 days], and day 21 (recovery, IQR 13–32 days). Twenty-one (64%) patients showed classical type of TC with akinesis of mid-left ventricular (LV) and apical segments and 12 (36%) of patients presented with mid-LV variant with apical sparing. Myocardial deformations were serially assessed using 2D strain analysis. All echocardiographic values on day 21 were compared with the corresponding values from 30 controls of similar age and gender. Results: LV ejection fraction (EF) gradually improved at follow-up (32 ± 8% on day 1 vs. 62 ± 4% on day 21, p  < 0.001). Despite no difference in LVEF between the patients with complete recovery (LVEF >60% on day 21) and controls, the patients showed significantly lower global longitudinal strain than controls. On regional analysis of the mid-LV segments, both longitudinal and circumferential strains of patients with TC were similarly diminished on day 1. During recovery, longitudinal strain showed more delayed recovery than circumferential strain compared to the values of controls. In LV apex of controls, circumferential strain normally presented higher value than longitudinal strain. In LV apex of patients with classical TC, the reduced circumferential strain on day 1 rapidly increased with a wide variation to maintain augmented circumferential shortening. Conclusions: Quantifying LV myocardial deformation in patients with TC is informative in the detection of persistent subtle LV dysfunction and improves our understanding of regional myocardial mechanics during recovery.